Reasons for officiating soccer: the role of passion-based motivations among Norwegian elite and non-elite referees - Johansen, B. T. (Movement & Sport Sciences - Science & Motricité, 2015)
This study examines the reasons for officiating soccer among Norwegian elite and non-elite referees. Eighty-three elite referees and 44 non-elite referees completed a web-based questionnaire (SurveyXact) that solicited their three main reasons for officiating soccer. The data were obtained by bracketing, intuiting, and describing their different reasons. Three main categories of descriptions emerged (percentage elite/non-elite): passion-based motivations (57/25%), social-based motivations (25/25%), and fitness-based motivations (13/31%). Norwegian elite referees are significantly more passion-based motivated than non-elite referees in the lower-level leagues. The prevalence of fitness-based motivations was significantly lower for elite referees than for non-elite referees. Social-based motivations had approximately the same importance for the two different groups of soccer referees.